Representation of the Mie Dialect in Japanese Popular Media: A Lingusitic Analysis of Yatogame-chan Kansatsu Nikki - Annurkhe Pudat, Resta Neana; Nurjaleka, Lisda (Universitas Negeri Semarang, 2025)
A dicalect represents a regional variation of a language, distinguished by unique phonetic features, vocabulary, and grammatical structures. The Mie dialect, a branch of the Kansai dialect group classified under Nishi Nihon Hogen (Western Japanese dialects), embodies these regional linguistic characteristics. This study investigates the representation of the Mie dialect in the Japanese anime series Yatogame-chan Kansatsu Nikki, focusing on two linguistic aspects: word classes and word formation processes. Employing a descriptive qualitative approach, the study utilizes Tomita’s classification of word classes and Palter and Slotsve’s theory on Kansai dialect word formation to analyze the data. This study identifies 30 examples of Mie dialect usage across the series, with sentence-final particles (shujoshi) emerging as the most frequest category. In terms of word formation, the most common process involves complete transformation from standard Japanese vocabulary. The findings highlight how popular media portrays regional dialects and contribute to broader discussion on linguistic diversity and regional identity in contemporary Japan. This study underscores the importance of analyzing dialect representation in media to understand how regional linguistic features are maintained, adapted, or transformed within popular culture.